2022
DOI: 10.1002/lno.12191
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide production in the Chesapeake Bay

Abstract: Estuaries at the global scale are significant but highly uncertain sources of atmospheric nitrous oxide (N 2 O), which is an intense greenhouse gas and ozone depletion agent. As the largest estuary in the United States, the Chesapeake Bay is suggested to be a spatially and temporally variable source and sink of N 2 O. However, limited observations of N 2 O cycling preclude us from estimating and predicting its net N 2 O flux. To improve our mechanistic understanding of the processes that control the N 2 O flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 70 publications
2
21
1
Order By: Relevance
“…Relatively homogeneous vertical distributions of N 2 O that were nearly equilibrated with the atmosphere were observed at downstream station CB3 on both the CB2019 and CB2020 cruises (Figure 1b). N 2 O concentrations at upstream CB2 in 2019 fall were supersaturated (up to 160%), across the water column suggesting net N 2 O production, which is confirmed by the direct measurement of N 2 O production (Tang et al, 2022). In contrast, N 2 O concentrations at CB1.5 in 2020 summer showed a distinct pattern compared to the other stations.…”
Section: Physical and Biogeochemical Conditions And Abundance Of N 2 ...supporting
confidence: 62%
See 1 more Smart Citation
“…Relatively homogeneous vertical distributions of N 2 O that were nearly equilibrated with the atmosphere were observed at downstream station CB3 on both the CB2019 and CB2020 cruises (Figure 1b). N 2 O concentrations at upstream CB2 in 2019 fall were supersaturated (up to 160%), across the water column suggesting net N 2 O production, which is confirmed by the direct measurement of N 2 O production (Tang et al, 2022). In contrast, N 2 O concentrations at CB1.5 in 2020 summer showed a distinct pattern compared to the other stations.…”
Section: Physical and Biogeochemical Conditions And Abundance Of N 2 ...supporting
confidence: 62%
“…Here we conducted the first direct measurements of N 2 O reduction rates in estuarine water, using the largest estuary in the United States, the Chesapeake Bay, as a model system to evaluate N 2 O reduction dynamics. When combined with concurrent measurements of N 2 O production by Tang et al, 2022, a comprehensive picture of N 2 O cycling is revealed. The in situ anoxic waters were observed to actively reduce N 2 O and the N 2 O reduction rate was higher than the N 2 O production rate, leading to N 2 O undersaturation in anoxic waters.…”
Section: Discussionmentioning
confidence: 99%
“…36 Some researchers indicated that nitrification primarily dominated N 2 O production in oxic natural waters, such as oceans and lakes, whereas denitrification prevailed in hypoxic/anoxic waters. 37,38 As such, we speculate that from clear to turbid waters, increased concentrations of suspended particles caused more suboxic microsites for denitrifiers to produce N 2 O. This result implies that denitrification might dominate N 2 O production in turbid water columns, where the occurrence of denitrification has been widely reported.…”
Section: N 2 O Emissions In Thementioning
confidence: 78%
“…All data were first normalized around zero before calculating the Pearson's correlation coefficient. Gene abundances (nirS and amoA) used for the RDA and correlation analyses were measured as previously described (Peng et al, 2015;Jayakumar et al, 2009;Tang et al, 2022). In the results and discussion sections, results are classified as shallow boundary or ODZ core waters according to a previously published threshold (Babbin et al, 2020) (Babbin et al, 2020).…”
Section: Redundacy Analysis (Rda) Principle Component Analysis (Pca) ...mentioning
confidence: 99%